2013
DOI: 10.1586/17476348.2014.854168
|View full text |Cite
|
Sign up to set email alerts
|

Use of breath-actuated inhalers in patients with asthma and COPD – an advance in inhalational therapy: a systematic review

Abstract: The pressurized metered dose inhalers and dry powder inhalers are the most widely used devices for inhalation therapy in asthma and chronic obstructive pulmonary disease; each of these devices have certain advantages and disadvantages that impact their use. Motivation from the virtues of these devices led to the development of breath-actuated or breath-activated metered dose inhalers. A history of the breath-actuated inhalers, the development and technical aspects, studies about the usability, inhalation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
0
32
0
1
Order By: Relevance
“…(6) BAIs were developed to eliminate the need for coordination of inhalation and actuation and produce higher drug deposition compared with DPIs. (11) The present study demonstrated that single doses of beclomethasone dipropionate 320 mcg delivered through the simple-to-use BAI were bioequivalent to beclomethasone dipropionate 320 mcg delivered through the MDI, and that the BAI allows for easy delivery for patients who may have difficulty coordinating inhalation with actuation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…(6) BAIs were developed to eliminate the need for coordination of inhalation and actuation and produce higher drug deposition compared with DPIs. (11) The present study demonstrated that single doses of beclomethasone dipropionate 320 mcg delivered through the simple-to-use BAI were bioequivalent to beclomethasone dipropionate 320 mcg delivered through the MDI, and that the BAI allows for easy delivery for patients who may have difficulty coordinating inhalation with actuation.…”
Section: Discussionmentioning
confidence: 59%
“…Patients often find BAIs easier to use than pressurized MDIs. (11) The present pharmacokinetics and bioequivalence study was conducted in healthy subjects because they represent the ideal model for conducting phase 1 pharmacokinetic studies without interference by concomitant pathological conditions. (12) In addition, crossover pharmacokinetic studies conducted in healthy subjects, similar to the present study, are regarded as the most suitable study design to assess bioequivalence between two products containing the same active ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation is the preferred route of administration for many drugs used in the treatment of COPD and inhalation devices are the main tools for effective delivery of inhaled agents (3). Advantages of delivering the drug directly via inhalation to where it would be effective are the facts that the amount of drug required can be decreased and systemic adverse events can be minimized within the effective dose range (3). Moreover, it has been reported that several factors may influence the approaches of patients with COPD to inhalation therapy and their preference of different devices (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that patients,who are using an inhaler that they prefer, would be more satisfied with treatment and would better comply with the drug, which would provide better clinical outcomes and decrease health expenditure (5,9). The most important issues considered in chose of inhalers have been reported to be the ease of use of device, inhalation technique, patient's preference, and cost-effectiveness (3,10). The present study aimed to assess frequency of misusage of inhalers and the affecting factors in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has a soft-triggering mechanism and gets actuated at lower inspiratory flow rates of approximately 27-30 L/min, which can be generated by almost all patients with OADs [14][15][16]. This helps Synchrobreathe overcome the key issues of both pMDIs (hand-breath coordination) and DPIs (high inspiratory flow required) with respect to optimal drug deposition [17].…”
mentioning
confidence: 99%